Seasonal variation in non-specific bronchial reactivity: a study of wheat workers with a history of wheat associated asthma. Issue 2 (February 1988) - Hensley, M J; Scicchitano, R; Saunders, N A; Cripps, A W; Ruhno, J; Sutherland, D; Clancy, R L
Abstract : To investigate seasonal variation in non-specific bronchial reactivity in wheat workers, we carried out histamine inhalation tests in 29 workers (28 of them men) from a small farming community with symptoms of wheat associated asthma before, during and after the 1983-4 Australian wheat harvest season. Four were cigarette smokers, and the age range was 12-54 (mean (SD) 30 (10)) years. Twenty eight subjects were atopic (one positive skinprick test result in tests with 10 common antigens), 60% reacting to house dust mite and all to at least one of eight wheat antigens. Baseline spirometry gave normal results (mean FVC1 90% (SD 8%) predicted; FVC 91% (7%) predicted). Bronchial reactivity was tested by the method of Yan et al. The cumulative doses of histamine acid phosphate (up to 3.91 mumol) that caused a fall of 20% from baseline in FEV1 was determined (PD20) and expressed as the geometric mean. In the low exposure season, May 1983, nine subjects had a PD20 (mean 1.2, range 0.3-3.9 mumol). The number rose to 19 in the summer harvest season, December 1983 (mean 0.8, range 0.07-3.9 mumol) and returned to nine in the subsequent winter, July 1984 (mean 1.8, range 0.4-3.9 mumol). The change in the number of subjects with a PD20 was significant (p less than 0.01). Four additional subjects probably had increased bronchial reactivity in the harvest season: in two the post-saline FEV1 was too unstable to give them histamine challenge and in two the challenge was inadvertently discontinued prematurely. Baseline FEV1 and FVC fell by 8% between the first and second studies (p less than 0.001); values were intermediate in the third study (FEV1 3.74, 3.44, and 3.57; FVC 4.66, 4.28, and 4.41 litres respectively). Linear modelling analysis of log PD20, season, FEV1, FVC, age, seasonality of asthma symptoms and skin test data indicated that the harvest season was the only significant determinant of variation in log PD20. It is concluded that in these wheat workers there is a seasonal variation in bronchial reactivity that may reflect a response to allergens associated with grain.